Miss Congeniality - Bullock, Sandra 1964-; Bullock, Sandra 1964-; Lawrence, Marc; Ford, Katie 1955-; Lucas, Caryn; Petrie, Donald (Warner Home Video, 2001)
Her legs are waxed, her lips are glossed, her gun is ready. FBI agent Gracie Hart id going undercover as one of the hopefuls eager to be the next Miss United States. But Gracie, whose idea of fashion accessory is the set of handcuffs she slaps onto the law breakers, doesn't have a beauty-pageant bone in her body. Sandra Bullock gets physical in Miss Congeniality, bringing her powerhouse talent for physical comedy to the role of an operative posing as a pageant contestant in order to ferret out a terrorist targeting the event. Michael Caine deliciously plays the frustrated consultant hired to turn the FBI's Dirty Harriet into a poised beauty.